Taxation of Multinationals and the ECJ. - Bond, S (Institute for Fiscal Studies, 2007)
Summary • Recent cases at the European Court of Justice have prompted changes to UK Controlled Foreign Companies rules and a broader consultation on the taxation of foreign profits. • The tax treatment of dividend income from overseas subsidiaries of UK companies is a complex but increasingly important area of the corporation tax system, given the growing importance of multinational firms. • The announced review is welcome and should be wide-ranging. It should consider the option of replacing the UK’s complex credit system with the simpler exemption system used in many other EU countries. Estimating the potential cost of this to the exchequer is extremely difficult and a matter of some debate. • Corporate tax rates have fallen faster in other EU countries than in the UK over the last decade, and particularly since 1999; this has contributed to growing concerns about the impact of UK corporation tax on business investment and location choices.